Trends and Developments in Inclusive Sports: A Bibliometric Perspective from Sports Sociology - Rahman, Revanza Rizky; Fitri, Mustika; Suherman, Adang; Apriady, Hilmy (Journal of Sport Science and Fitness, 2024)
Sports sociology, particularly in the context of inclusive sports, has become an important field in understanding social dynamics in an increasingly diverse modern society. Inclusive sports aim to accommodate various groups with different characteristics, such as people with disabilities, gender minorities, and specific age groups. This article uses bibliometric analysis to explore the development of research on sports sociology in inclusive sports. Through literature mapping obtained from the Scopus database, this research shows a significant increase in publications related to inclusive sports between 2013 and 2023, analyzing data from 794 articles published in various scientific journals.The analysis results reveal the dominance of topics related to "disability," "paralympic," and "inclusion" in the literature, highlighting efforts to enhance equal access and opportunities for people with disabilities in sports. This research also identifies leading authors and countries that have made significant contributions to the development of theory and practice in inclusive sports, as well as demonstrating the importance of international collaboration in expanding understanding of this issue. However, there are limitations in this research as it only uses data from Scopus, which may overlook literature from other sources, including research in developing countries. This research provides an overview of important trends and developments in inclusive sports sociology and opens opportunities for further research that is more inclusive.